Environmental DNA (eDNA) reveals the effects of cascade dam development on the distribution patterns of aquatic biodiversity in mountain rivers - Yanjun Shen; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Ruli Cheng (Frontiers in Marine Science, 2024)
The rich and special biodiversity in mountain rivers is experiencing a continuous decline due to the influence of climate change and anthropogenic factors. To explore the alterations in the distribution of aquatic biodiversity in mountain rivers in the context of cascade dam development, the environmental DNA (eDNA) metabarcoding technique was used to examine the aquatic biodiversity of the Wujiang River, a representative mountain river with an 11-stage cascade dam. In this study, a comprehensive analysis of aquatic organisms in the Wujiang River mainstem was conducted, and 17 phyla and 38 classes were detected in the 36 water samples. The most abundant group is the benthic organisms, and the least abundant group is the amphibians. The results of the diversity analysis showed a clear longitudinal distribution pattern of aquatic organisms along the altitudinal gradient, with higher richness of aquatic organism communities the further to the lower reaches. Meanwhile, RDA analysis revealed that altitude, dissolved oxygen, reservoir length, and reservoir construction time were the key environmental factors influencing the distribution of aquatic organisms in the Wujiang River mainstem. The findings of this research also showed the applicability of the eDNA method in detecting aquatic biodiversity.

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

Application of eDNA metabarcoding for monitoring the fish diversity of the Jiangjin to Fuling section of the upper reaches of the Yangtze River - Ruli Cheng; Yang Luo; Qinghua Li; Yufeng Zhang; Zhihao Liu; Qiliang Chen; Yingwen Li; Yanjun Shen (Hydrobiologia, 2023)

Genetic Diversity of Jinshaia sinensis (Cypriniformes, Balitoridae) Distributed Upstream of the Yangtze River - Yang Luo; Yufeng Zhang; Ruli Cheng; Qinghua Li; Yu Zhang; Yingwen Li; Yanjun Shen (Fishes, 2023)
The upper reaches of the Yangtze River (upper YR) are a biological zone with extremely rich fish diversity, especially endemic fish. However, long-term human interference, such as environmental pollution and cascade hydropower construction, has significantly changed the habitat of many fish and is threatening the number and genetic diversity of fish populations. Jinshaia sinensis is a typical small and endemic but rare fish that is found in the upper YR, and its genetic diversity and structure still need further study. To understand the current levels of genetic diversity in J. sinensis, we analyzed the genetic diversity, population history, genetic structure, etc., of three J. sinensis populations based on two mitochondrial genes (the cytochrome-c oxidase subunit I, COI, and cytochrome-b gene, Cytb) and two nuclear genes (recombination-activating protein 1, RAG1, and rhodopsin, RH). The genetic diversity analysis indicated that J. sinensis had high genetic diversity, with high haplotype diversity (h) and nucleotide diversity (Pi). Population pairwise FST analysis revealed a significant genetic divergence between the Lijiang and Luzhou populations for all genes and between the Panzhihua and Luzhou populations, except for the COI gene; however, analyses of molecular variance (AMOVA) showed no significant geographic genetic structure among populations, and gene flow analysis also indicated a certain degree of gene exchange among populations. Haplotype network structure analyses revealed low levels of shared haplotypes among populations. Neutrality test and mismatch distribution results indicated that only the Lijiang population had experienced obvious population expansion. Overall, these results indicate that J. sinensis is still a single evolutionarily significant unit, but when considering the threat of habitat disturbance to the population, it is still necessary to carry out long-term genetic monitoring on J. sinensis and on other endemic fishes with similar ecological habits in order to maintain the genetic diversity of fishes in the upper YR.